2023
DOI: 10.1007/s00404-023-07163-w
|View full text |Cite|
|
Sign up to set email alerts
|

Hysteroscopic versus histopathological agreement in the diagnosis of chronic endometritis: results from a retrospective observational study

Belén Almoguera Pérez-Cejuela,
Salvatore Giovanni Vitale,
Tirso Pérez-Medina
et al.

Abstract: Purpose To evaluate the agreement rate between hysteroscopy and pathological examination in case of chronic endometritis. Methods A retrospective observational study carried out at Gynecology and Obstetrics Department, Puerta de Hierro Hospital, Autónoma University of Madrid, Spain, from January 2021 to June 2022 was performed by obtaining data from 115 medical records of women who underwent office hysteroscopies that was compared with the findings of fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…reported that the diagnostic discordance rate for CE between hysteroscopic findings and endometrial histopathology was high, at 58.5% (2018), which also implies a low diagnostic concordance rate [ 2 ]. A low concordance rate between hysteroscopic findings and histological examination was reported more recently, with the authors concluding that hysteroscopic signs are not yet sufficient to make an accurate diagnosis of CE [ 22 ]. The view that hysteroscopy alone cannot accurately diagnose CE is corroborated by further studies [ 15 , 18 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…reported that the diagnostic discordance rate for CE between hysteroscopic findings and endometrial histopathology was high, at 58.5% (2018), which also implies a low diagnostic concordance rate [ 2 ]. A low concordance rate between hysteroscopic findings and histological examination was reported more recently, with the authors concluding that hysteroscopic signs are not yet sufficient to make an accurate diagnosis of CE [ 22 ]. The view that hysteroscopy alone cannot accurately diagnose CE is corroborated by further studies [ 15 , 18 , 23 ].…”
Section: Discussionmentioning
confidence: 99%